Assessing the impact of the graduation approach in the Philippines. - Schelzig, Karin; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
The graduation approach builds on a foundation of social assistance with a holistic set of poverty reduction interventions. From 2018 to 2020, an ADB project piloted the approach for 1,800 households in Negros Occidental, with a focus on group based coaching and group based asset delivery. The brief explains key results, including how household resilience to COVID-19 was improved across a range of dimensions. It also highlights implementation challenges and key lessons.
Keywords: Philippines -- Social assistance programs; Poverty -- Philippines; Economic development; Poverty -- International cooperation; Electronic book